Capacity enhancement for cellular CDMA - Cheah, Christopher Kok Leong. (2010)
In this thesis, a generic DS-CDMA cellular system was first modeled and analyzed with emphasis on Rayleigh fading, uniform user distribution, path loss and power control. Initial results revealed that the number of mobile users supported by the reverse link is significantly smaller than that of the forward link, which creates a bottleneck in the overall cellular capacity. This observation motivated that appro-priate signal-processing techniques must be incorporated to approximately balance the quality levels of these two links. In particular, three capacity enhancement schemes, namely, bandwidth allocation, antenna diversity and multiuser detection were explored in detail.